2002
DOI: 10.1053/jhep.2002.31777
|View full text |Cite
|
Sign up to set email alerts
|

Varied assembly and RNA editing efficiencies between genotypes I and II hepatitis D virus and their implications

Abstract: The mechanisms that link genotypes of hepatitis D virus (HDV) with clinical outcomes have not yet been elucidated. Genotypic variations are unevenly distributed along the sequences of hepatitis delta antigens (HDAgs). Of these variations, the packaging signal at the Cterminus has a divergence of 74% between genotypes I and II. In this report, we address the issue of whether these high variations between genotypes affect assembly efficiency of HDV particles and editing efficiency of RNA. Viral package systems o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
64
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 41 publications
3
64
0
Order By: Relevance
“…In general, genotype 3 appears to be associated with the most severe disease course, while genotype 2 seems to be associated the least severe outcomes (6,7,13). A previous study comparing the efficiency of HDAg-L incorporation into VLPs for genotypes 1 and 2, but not genotype 3, proposed a direct correlation between the low assembly efficiency of HDV genotype 2 and its low virulence relative to genotype 1 (13).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In general, genotype 3 appears to be associated with the most severe disease course, while genotype 2 seems to be associated the least severe outcomes (6,7,13). A previous study comparing the efficiency of HDAg-L incorporation into VLPs for genotypes 1 and 2, but not genotype 3, proposed a direct correlation between the low assembly efficiency of HDV genotype 2 and its low virulence relative to genotype 1 (13).…”
Section: Discussionmentioning
confidence: 96%
“…Among the three distinct HDV genotypes that have been identified, significant differences in the severity of disease observed in infected patients have been reported (6,7,13). In general, genotype 3 appears to be associated with the most severe disease course, while genotype 2 seems to be associated the least severe outcomes (6,7,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although an association between HDV-1/HBV-A and -D and HDV-3/HBV-F and -A has been observed, independent investigations suggest that the co-infections are mainly representative of common genotypes of each of the viruses in certain geographical areas and not specific for distinct HBV or HDV genotypes [13][14][15] . Studies indicate that HDV genotype 2 is associated with a less aggressive disease compared to genotype 1 which has been attributed to the higher packaging efficiency of genotype 1 than that of genotype 2 [16,17] . Moreover, a variation in the packaging efficiency has been observed among different isolates of the same genotype, which reflects the critical role of this length in HDAg interactions with HBsAg.…”
Section: Hbsag-hdag Interactionsmentioning
confidence: 99%
“…Moreover, a variation in the packaging efficiency has been observed among different isolates of the same genotype, which reflects the critical role of this length in HDAg interactions with HBsAg. It has been reported that the hydrophobic nature of the L-HDAg C-terminal domain provided by C211-farnesylation as well as the number of hydrophobic residues of the packaging signal (which differs among HDV genotypes) enhance HDV interactions with surface proteins of HBV and therefore the packaging efficiency [17] .…”
Section: Hbsag-hdag Interactionsmentioning
confidence: 99%